Presence of pathogenic bacteria in faeces from dogs fed raw meat-based diets or dry kibble. (13th February 2020) - Runesvärd, Ellinor; Wikström, Camilla; Fernström, Lise-Lotte; Hansson, Ingrid
Abstract : Background: Feeding dogs with raw meat-based diets (RMBD) has increased in popularity in recent years. Proponents claim that RMBD is more natural for dogs, because it is what their ancestors (wolves) eat. Opponents claim that RMBD is a health hazard to both humans and animals, with a risk of spreading zoonotic bacteria and resistant bacterial strains. Methods: This cross-sectional study investigated differences in bacteria shedding in faeces between dogs fed RMBD and dogs fed dry kibble. Faeces samples from 50 dogs from the same municipality were analysed for the presence of extended-spectrum beta-lactamases (ESBL)-producing Escherichia coli, Campylobacter and Salmonella . Results: For the 25 dogs fed RMBD, ESBL E coli was isolated from 13 faeces samples, Campylobacter from 12 and Salmonella from 1. For the 25 dogs fed dry kibble, ESBL-producing E coli was isolated from one faeces sample and Campylobacter from four, while Salmonella was not detected. Conclusion: There was thus a significant difference in excretion of zoonotic and resistant bacteria in faeces between dogs fed RMBD and dogs fed dry kibble. These results confirm that RMBD can pose a microbiological risk not only for dogs, but also for people handling RMBD and faeces from dogs.